2017
DOI: 10.1186/s12876-017-0601-1
|View full text |Cite
|
Sign up to set email alerts
|

Costs and quality of life of small-incision open cholecystectomy and laparoscopic cholecystectomy - an expertise-based randomised controlled trial

Abstract: BackgroundHealth care providers need solid evidence based data on cost differences between alternative surgical procedures for common surgical disorders. We aimed to compare small-incision open cholecystectomy (SIOC) and laparoscopic cholecystectomy (LC) concerning costs and health-related quality of life using data from an expertise-based randomised controlled trial.MethodsPatients scheduled for cholecystectomy were assigned to undergo LC or SIOC performed by surgeons in two different expert groups. Total cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Hence novel techniques such as the Single Incision Laparoscopic Surgery (SILS) or robotic single-site cholecystectomy (RSSC) are increasingly seen as essential and relevant to patient needs. While SILS cholecystectomy is associated with better cosmesis and post-operative pain,26 there is an increased risk of an incisional hernia, and some trials have failed to demonstrate a difference in QoL, despite being a more costly procedure 27. Our study shows that scar cosmesis is not a high priority outcome for patients and future clinical trials to evaluate these newer surgical techniques should focus on the improvement in QoL rather than cosmesis and body image scores.…”
Section: Discussionmentioning
confidence: 71%
“…Hence novel techniques such as the Single Incision Laparoscopic Surgery (SILS) or robotic single-site cholecystectomy (RSSC) are increasingly seen as essential and relevant to patient needs. While SILS cholecystectomy is associated with better cosmesis and post-operative pain,26 there is an increased risk of an incisional hernia, and some trials have failed to demonstrate a difference in QoL, despite being a more costly procedure 27. Our study shows that scar cosmesis is not a high priority outcome for patients and future clinical trials to evaluate these newer surgical techniques should focus on the improvement in QoL rather than cosmesis and body image scores.…”
Section: Discussionmentioning
confidence: 71%
“…For benign gallbladder disease, minilaparotomy cholecystectomy (MC) provides an excellent alternative to laparoscopic cholecystectomy (LC). When compared to LC, MC is cheaper [7,15] and faster [7] [16]. It is safe in the obese [16] and as an emergency procedure [17].…”
Section: Discussionmentioning
confidence: 99%
“…It is safe in the obese [16] and as an emergency procedure [17]. Research has shown that LC and MC have similar outcomes when looking at mortality [7], complications [7], cosmesis [18], quality of life [15] and same-day surgery rates [19]. When compared to MC, LC offers limited or no advantages to the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies on QoL after GSD surgery have concerned surgical approach [12][13][14][15][16] , patient-related factors 4,7 , or timing of the procedure [17][18][19] . Studies on the impact of cultural differences on QoL of patients with pathologies other than GSD have been performed [20][21][22][23] .…”
Section: Discussionmentioning
confidence: 99%